Framing a Well-Structured Single Best Response Multiple Choice Questions (MCQs) - An Art to be Learned by a Teacher - Chaudhary, N; Bhatia, BD; Mahato, SK (Journal of Universal College of Medical Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jucms.v2i2.11176 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 60-64